Chiral and achiral analysis of chiral flavonoids with liquid and supercritical fluid chromatography – A review - Laurine Réset; Clément De Saint Jores; Caroline West (Journal of Chromatography Open)
Flavonoids have been the topic of numerous studies for decades because they possess varied interesting bioactivities including e.g. antioxidant and anticancer properties. In particular, some flavonoids possess chiral features, due to the presence of one or two chiral carbon atoms on their aglycone root. They include flavans, isoflavans, flavanones, flavanonols, flavanols and auronols. In addition, other chirality centres may be observed on the carbohydrate groups attached to the aglycone root, but these will not be considered in the present paper. However, as stereoisomers usually have different bioactivity, analysis methods focusing on these specific flavonoid classes should be of interest to better understand their mode of action and their biosynthetic pathways. In the present review, we have examined chromatographic analyses in the liquid phase (LC) and the supercritical phase (SFC) in achiral and chiral modes to analyse chiral flavonoids. One- and two-dimensional methods are reported, and the different detection modes are also examined. Note that this review did not aim at being comprehensive, but rather at displaying the diversity and main features of current methods.